Somatic hybridization provides segregating populations for the identification of causative mutations in sterile mutants of the moss Physcomitrella patens - Moody, LA; Kelly, S; Coudert, Y; Nimchuk, ZL; Harrison, CJ; Langdale, JA (Wiley, 2018)
Forward genetics is now straightforward in the moss Physcomitrella patens, and large mutant populations can be screened relatively easily. However, perturbation of development before the formation of gametes currently leaves no route to gene discovery. Somatic hybridization has previously been used to rescue sterile mutants and to assign P. patens mutations to complementation groups, but the cellular basis of the fusion process could not be monitored, and there was no tractable way to identify causative mutations. Here we use fluorescently tagged lines to generate somatic hybrids between Gransden (Gd) and Villersexel (Vx) strains of P. patens, and show that hybridization produces fertile diploid gametophytes that form phenotypically normal tetraploid sporophytes. Quantification of genetic variation between the two parental strains reveals single nucleotide polymorphisms at a frequency of 1/286 bp. Given that the genetic distinction between Gd and Vx strains exceeds that found between pairs of strains that are commonly used for genetic mapping in other plant species, the spore populations derived from hybrid sporophytes provide suitable material for bulk segregant analysis and gene identification by genome sequencing.